PENERAPAN NORMA KEDISIPLINAN OLEH SISWA DI MADRASAH ALIYAH NEGERI 1 PONTIANAK - Yusni Ramdhani; Rustiyarso Rustiyarso; Supriadi Supriadi (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine the application of disciplinary norms by students of class XI IPS in Madrasah Aliyah Negeri 1 Pontianak. The research method used is descriptive with a form of qualitative research. The data source of this study consisted of primary data sources obtained from interviews with the Student Waka, BK teachers and students of class XI IPS. Whereas secondary data is obtained by examining archives / documents in the form of picket books and case books. The results showed that the Application of Disciplinary Norms by Social Sciences Grade XI students in Madrasah Aliyah Negeri 1 Pontianak was carried out well. This is evidenced by there are several forms of application given, namely in the form of school rules such as: student discipline not late coming and entering school, neatness of students in dressing, praying in congregation, and following extracurricular activities in accordance with the interests of each student. The main factors causing students' discipline in class XI IPS are students who are not aware of the importance of disciplinary norms and lack of discipline in controlling themselves to comply with school rules. The effectiveness of the enforcement of disciplinary norms in Madrasah Aliyah Negeri 1 in the last year (2019) has gone well. Keywords : Implementation, Disciplinary Norms, Madrasah Aliyah.